The Search for Antidotes Against Ricin - Botelho, Fernanda Diniz; Franca, Tanos Celmar Costa; LaPlante, Steven R (Mini reviews in medicinal chemistry, 2024)
The castor plant (Ricinus communis) is primarily known for its seeds, which contain a unique fatty acid called ricinoleic acid with several industrial and commercial applications. Castor seeds also contain ricin, a toxin considered a chemical and biological warfare agent. Despite years of investigation, there is still no effective antidote or vaccine available. However, some progress has been made, and the development of an effective treatment may be on the horizon. To provide an updated overview of this issue, we have conducted a comprehensive review of the literature on the current state of research in the fight against ricin. This review is based on the reported research and aims to address the challenges faced by researchers, as well as highlight the most successful cases achieved thus far. Our goal is to encourage the scientific community to continue their efforts in this critical search.
Keywords: chemical warfare; ricin A chain; ribosome-inactivating protein.; ricin; Ricin; Chemical Warfare Agents; Humans; Animals; Ricin inhibitors; lidé; zvířata; drug design; antidota; Antidotes; medicinal chemistry; chemické bojové látky